A sociodemographic profile of inmates of an old age home in North Maharashtra - Chauhan, Rambadan Phoolchand; Patil, Sunil Vitthalrao (International Journal Of Community Medicine And Public Health, 2019)
Background: India had about 8.6 crores elderly above 65 years in 2016. It is expected to increase to 17.9 crores by 2031 and 30.1 crores by 2051. This will increase the demand for health and other social security services. Hence, we decided to collect and analyze socio-demographic profile of inmates of an old age home (OAH). Methods: Cross sectional study was conducted at an old age home in North Maharashtra from 15th March 2008 to 30th April 2008 by questionnaires/interviews. Sample size was 100%. Results: There were total 40 inmates. 50% were aged 50-60 years. 27.5% (60-70 years), 17.5% (70-80 years) and 5% (80-90 years). Males were 52.5%, female- 47.5%. married- 50%, widow- 45% and unmarried- 5%. 30% were housewives, 27.5 % were labourers, 20% were businessmen, 10% were in government jobs, 7.5% were teachers and 5% were farmers. 40% inmates were childless, >4 children- 25%, 3 children- 17.5%, 2 children- 12.5% and 1 child-5%. 33 inmates’ children were literate while 7 inmates’ children were illiterate. Main causes of staying at OAH were family problems 50%, personal cause 45% and economical cause was 5%. Major health problems were locomotor disorder- 52.5%, cataract- 47.5%, hypertension- 17.5%, diabetes- 15%, genito-urinary problem- 7.5%, decreased hearing- 7.5%, IHD- 5% and respiratory problems- 2.5%. Dental health/problems included missing teeth- 65%, caries- 25%, discoloration- 22.5% and dentures- 20%. Literacy was 70%. Conclusions: Major medical/dental/social problems were locomotor, cataract, diabetes-mellitus, hypertension, tooth loss, caries, family disputes, poverty and childlessness.